2021
DOI: 10.1021/acs.inorgchem.1c01081
|View full text |Cite
|
Sign up to set email alerts
|

{Cu8} Cluster-Sandwiched Polyoxotungstates and Their Polymers: Syntheses, Structures, and Properties

Abstract: Four inorganic−organic hybrid octa-Cu cluster sandwiched polyoxotungstates (POTs), [Cu 8 4) (en = ethylenediamine), were hydrothermally made and characterized by single-crystal X-ray diffraction, infrared spectra, powder X-ray diffraction, and thermogravimetric analysis, respectively. Structure analysis reveals that the polyoxoanion of 1/2 is a discrete dimer built by two trivalent Keggin [B-α-XW 9 O 34 ] 10− (X = Si/ Ge) fragments and one octa-Cu cluster, whereas 3 and 4 display a twodimensional network bui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…Compared with these catalysts, the new catalyst 1 simultaneously exhibited distinguished conversion, outstanding yield, and good recyclability for the complete oxidation to sulfone with the assistance of the green oxidant H 2 O 2 under mild conditions. Moreover, the catalytic efficiency of 1 is superior to that of most transition metal substituted POMs reported previously. ,,, …”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Compared with these catalysts, the new catalyst 1 simultaneously exhibited distinguished conversion, outstanding yield, and good recyclability for the complete oxidation to sulfone with the assistance of the green oxidant H 2 O 2 under mild conditions. Moreover, the catalytic efficiency of 1 is superior to that of most transition metal substituted POMs reported previously. ,,, …”
Section: Resultsmentioning
confidence: 72%
“…Moreover, the catalytic efficiency of 1 is superior to that of most transition metal substituted POMs reported previously. 21,32,60,61 As proposed in the reaction mechanism (Figure S10), we speculated that the oxidant H 2 O 2 could react with POMs to obtain the active electrophilic peroxide intermediates, which facilitated the oxidation process. As the sulfides or sulfoxides captured oxygen atoms, the peroxide POM intermediates were reduced to the original POMs for the next cycles.…”
Section: ■ Experimental Sectionmentioning
confidence: 87%
“…The electrochemical properties of complexes 1–4 have been studied in 0.1 M H 2 SO 4 + 0.5 M Na 2 SO 4 aqueous solution. 30 We used 1 -, 2 - and 4 -CPEs as examples, owing to the similar electrochemical behaviors between 2 - and 3 -CPEs. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, IR spectra (Figure S19) and PXRD patterns (Figure S20) confirmed that 1 could maintain its structural integrity after catalytic reactions. Finally, in light of previous literature reports , and our results, a plausible oxidation mechanism has been summarized in Scheme S2.…”
Section: Resultsmentioning
confidence: 99%